2015
DOI: 10.3949/ccjm.82a.14026
|View full text |Cite
|
Sign up to set email alerts
|

ST-segment elevation: Differential diagnosis, caveats

Abstract: The differential diagnosis of ST-segment elevation includes four major processes: ST-segment elevation myocardial infarction (STEMI); early repolarization; pericarditis; and ST elevation secondary to an abnormality of the QRS complex (left bundle branch block, left ventricular hypertrophy, or preexcitation). Other processes that may be associated with ST elevation include hyperkalemia, pulmonary embolism, and Brugada syndrome. The clinical setting and specific electrocardiographic criteria often allow identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 40 publications
1
45
0
5
Order By: Relevance
“…As a sign of myocardial ischemia, the change of ST segment elevation can reflect the degree of ischemic injury during coronary artery occlusion . The diagnosis of ST segment elevation includes different processes, such as ST segment elevation myocardial infarction and pericarditis . Some studies have demonstrated that exposure to PM air pollution was associated with ST segment elevation and can trigger acute coronary events, especially myocardial infarction associated with ST segment elevation (STEMI) .…”
Section: Discussionmentioning
confidence: 99%
“…As a sign of myocardial ischemia, the change of ST segment elevation can reflect the degree of ischemic injury during coronary artery occlusion . The diagnosis of ST segment elevation includes different processes, such as ST segment elevation myocardial infarction and pericarditis . Some studies have demonstrated that exposure to PM air pollution was associated with ST segment elevation and can trigger acute coronary events, especially myocardial infarction associated with ST segment elevation (STEMI) .…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis for ST-elevation includes STEMI, aortic dissection, pulmonary embolism, stress (takotsubo) cardiomyopathy, pericarditis with or without effusion, myocarditis, hypercalcemia, hyperkalemia, coronary vasospasm, coronary artery dissection, left ventricular aneurysm, left ventricular hypertrophy, the Brugada syndrome, left bundle branch block, early repolarization, early post-cardioversion, intracranial hemorrhage, and rarely, tumor invasion of the heart 3,4,5,6 .…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Despite being broadly available for more than a century, its composition remains unchanged, as does its place as a first line diagnostic exam in the approach of many cardiac diseases, being irreplaceable in the evaluation of thoracic pain syndromes. However, like in every diagnostic exam, the clinical context must never be dismissed, as many situations other than acute myocardial infarction (normal variant, pericarditis, hyperkalemia, and pulmonary embolism) may cause ST-segment elevation [1,2]. This clinical interpretation, being decisive for the immediate treatment of the ST-segment elevation myocardial infarction (STEMI), becomes of paramount importance in hospitals without conditions for primary angioplasty.…”
Section: Introductionmentioning
confidence: 99%